2022
DOI: 10.1038/s41467-022-29768-6
|View full text |Cite
|
Sign up to set email alerts
|

Periodic corner holes on the Si(111)-7×7 surface can trap silver atoms

Abstract: Advancement in nanotechnology to a large extent depends on the ability to manipulate materials at the atomistic level, including positioning single atoms on the active sites of the surfaces of interest, promoting strong chemical bonding. Here, we report a long-time confinement of a single Ag atom inside a corner hole (CH) of the technologically relevant Si(111)-7×7 surface, which has comparable size as a fullerene C60 molecule with a single dangling bond at the bottom center. Experiments reveal that a set of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The DASF substrate is simulated with a Si(111) slab with a super cell of p(7×7), which contains seven layers of Si in the Z direction and 298 Si atoms. The bottom of the DASF substrate is passivated with one layer of 49 hydrogen atoms after optimizing the Si-H bonds, because hydrogen-termination of Si dangling bonds is one of the most common and useful methods of producing a chemically passivated surface [33][34][35][36][37]. During the optimization of the positions of Fe atoms, two bottom layers of Si together with the hydrogen atoms are fixed to model the bulk lattice properties, while the other Si atoms and Fe atoms are relaxed.…”
Section: Methodsmentioning
confidence: 99%
“…The DASF substrate is simulated with a Si(111) slab with a super cell of p(7×7), which contains seven layers of Si in the Z direction and 298 Si atoms. The bottom of the DASF substrate is passivated with one layer of 49 hydrogen atoms after optimizing the Si-H bonds, because hydrogen-termination of Si dangling bonds is one of the most common and useful methods of producing a chemically passivated surface [33][34][35][36][37]. During the optimization of the positions of Fe atoms, two bottom layers of Si together with the hydrogen atoms are fixed to model the bulk lattice properties, while the other Si atoms and Fe atoms are relaxed.…”
Section: Methodsmentioning
confidence: 99%
“…We also found some up-and down-spin states above the Fermi energy, which may be because of the anti-bonding of the Ag atoms with the Zr and O atoms. 39,40 Additionally, the visualization of the spin densities, as shown in Figure S5, of the Ag/ZrO 2 systems demonstrated that the Ag atoms became less positively charged after loading. In the Ag 8 /ZrO 2 system, the spin densities with the d orbital of Zr atoms and the p-orbital characteristics of O atoms were found to be localized around the Ag atoms, evidencing the chemical bonding between Ag and ZrO 2 .…”
Section: Properties Of Ag/zro 2 With Different Ag Surfacementioning
confidence: 98%
“…16 It can be prepared by heating Si(111) wafers up to 1490 K in a sample preparation chamber, and then quickly cooling down to room temperature. 17 Due to the existence of Si dangling bonds on the surface, Si(111)-(7 × 7) is an ideal template for self-assembled growth of large quantities of nearly identical clusters with intriguing electronic structures. Various identical transition metal clusters, including Co, Na, Fe, Cu, Ag, Mn, Au, Cd and other metal elements, have been successfully deposited on the Si(111)-(7 × 7) surface, which hold sizes of 3–25 atoms as “magic numbers”.…”
Section: Introductionmentioning
confidence: 99%